Cognitive Processing of Meaning in Language in Brain during English Comprehension - Ira Tiara Rahayu; Lusiana Suciati Dewi (Teaching English and Language Learning English Journal, 2026)
Language is a complex cognitive system that functions not only as a means of communication but also as a mental process occurring in the human brain. This study examines the cognitive processing of meaning within a linguistic framework in the brain during English comprehension among English as a Foreign Language (EFL) learners. The study focuses on how learners actively process and construct meaning when exposed to English input. From a neurocognitive perspective, this process involves the interaction of multiple brain regions responsible for language processing, memory retrieval, semantic interpretation, and contextual integration, indicating that comprehension is supported by distributed neural networks rather than a single localized area. The study uses a qualitative approach with a think-aloud protocol to capture learners' cognitive processes in real-time while completing a video-based comprehension task. The findings indicate that comprehension involves dynamic cognitive activities such as translating, inferring meaning, predicting content, and utilizing contextual and visual cues. These processes demonstrate that language comprehension is not passive but requires active mental engagement and the integration of prior knowledge with new input. In addition, the brain continuously coordinates these processes through simultaneous neural activation, enabling learners to construct meaning efficiently. The study highlights that multiple cognitive mechanisms operate simultaneously in the brain during language comprehension. Furthermore, the study emphasizes the importance of focusing on learners' internal processing rather than solely on the final comprehension outcome. The results provide deeper insights into how language is processed in the brain and suggest that teaching strategies should align with brain-based learning principles, supporting active cognitive engagement to enhance the effectiveness of language learning.